Smart Posture Correcter (SPC) / Nur Hidayah Marzuki, Ainin Nur Iffah Mohamad Baharudin … [et al.] - MARZUKI, NUR HIDAYAH; MOHAMAD BAHARUDIN, AININ NUR IFFAH; YAHAYA, NABILAH; MOHD NOOR, NURUL HUDA; ABD.RAHIM, NOR FATIN AFIFAH (2018)
The team is developing a Smart Posture Corrector (SPC). SPC is a corset that is useful as itprovides ergonomic purpose in human body. The idea of this product are to keep our body inperfect alignment, maintaining the spine's natural curvature, with our neck straight andshoulders parallel with hips.